Vertigoheel improves central vestibular compensation after unilateral peripheral vestibulopathy in rats - Hatat, Bérénice; Boularand, Romain; Bringuier, Claire; Chanut, Nicolas; Besnard, Stéphane; Mueller, Andrea M.; Weyer, Kathrin; Seilheimer, Bernd; Tighilet, Brahim; Chabbert, Christian (Frontiers in Neurology, 2022)
The aim of this study was to assess the effect of Vertigoheel on central vestibular compensation and cognitive deficits in rats subjected to peripheral vestibular loss. Young adult male Long Evans rats were subjected to bilateral vestibular insults through irreversible sequential ototoxic destructions of the vestibular sensory organs. Vestibular syndrome characteristics were monitored at several time points over days and weeks following the sequential insults, using a combination of behavioural assessment paradigms allowing appreciation of patterns of change in static and dynamic deficits, together with spatial navigation, learning and memory processes. Vertigoheel administered intraperitoneally significantly improved maximum body velocity and not moving time relative to its vehicle control at day two and three and at day two, respectively, after unilateral vestibular lesion (UVL). It also significantly improved postural control relative to its vehicle one day after UVL. Conversely, Vertigoheel did not display any significant effect vs vehicle on the severity of the syndrome, nor on the time course of other examined parameters such as distance moved, mean body velocity, meander, and rearing. Spatial cognition testing using Y- and T-maze and eight-radial arm maze did not show any statistically significant difference between Vertigoheel and vehicle groups. However, Vertigoheel potentially enhanced the speed of learning in Sham animals. Evaluating Vertigoheel’s effect on thigmotaxis during the open-field video tracking test revealed no significant difference between Vertigoheel and its vehicle control groups suggesting that Vertigoheel does not seem to induce sedative or anxiolytic effects that could negatively affect vestibular and memory function. Present observations reveal that Vertigoheel improves central vestibular compensation following unilateral peripheral vestibular loss as demonstrated by improvement of specific symptoms.